Value of long-term LNG contracts: A theoretical and empirical study - Xia, Xiaoning; Wu, Rui; Liu, Yan; Wu, Jinzhou; Lu, Tiankuo (Frontiers in Earth Science, 2023)
With the rapid development of short-term and spot trade of liquefied natural gas (LNG), the natural gas market is gradually evolving from regionalization to globalization. At the same time, the existence and rationality of long-term LNG contracts have become increasingly controversial. To explore the value of long-term LNG contracts in the process of natural gas market globalization, this article constructs a two-stage game model and applies China’s LNG trade data in 2018 to the model. The study shows that, compared with complete import of short-term LNG, even if the long-term LNG contracts do not have price advantages, importing an appropriate amount of long-term LNG may help to increase the total LNG imports, reduce the price of LNG, and thus improve import benefits. Besides, a moderate amount of long-term LNG contracts is conducive to the establishment of a stable and flexible natural gas supply system and the security of natural gas imports. Therefore, natural gas importers should not underestimate or even ignore the value of long-term LNG contracts while actively participating in short-term and spot trade of natural gas.